2000
DOI: 10.1136/ard.59.4.257
|View full text |Cite
|
Sign up to set email alerts
|

Sequential changes of KL-6 in sera of patients with interstitial pneumonia associated with polymyositis/dermatomyositis

Abstract: Objective-KL-6 is a mucin-like high molecular weight glycoprotein, which is strongly expressed on type II alveolar pneumocytes and bronchiolar epithelial cells. It has been demonstrated that the KL-6 antigen is a useful marker for estimating the activity of interstitial pneumonia. In this study, it is hypothesised that serum KL-6 is a useful marker to evaluate the activity of interstitial pneumonia associated with polymyositis/ dermatomyositis (PM/DM). Methods-KL-6 was measured in sera in 16 patients diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 11 publications
(5 reference statements)
2
46
1
1
Order By: Relevance
“…SP-D serum levels have been found to be higher in patients with PM/DM and ILD compared with patients without lung involvement and healthy controls [146]. Similarly, serum levels of KL-6, a glycoprotein expressed on type-II alveolar pneumocytes and bronchial epithelial cells, have been found to be increased in PM/DM patients with interstitial lung involvement when compared with patients without parenchymal disease and healthy controls [147]. Finally, SP-D is suggested to be a useful marker in patients with PM/DM [146].…”
Section: Serum Biomarkersmentioning
confidence: 78%
“…SP-D serum levels have been found to be higher in patients with PM/DM and ILD compared with patients without lung involvement and healthy controls [146]. Similarly, serum levels of KL-6, a glycoprotein expressed on type-II alveolar pneumocytes and bronchial epithelial cells, have been found to be increased in PM/DM patients with interstitial lung involvement when compared with patients without parenchymal disease and healthy controls [147]. Finally, SP-D is suggested to be a useful marker in patients with PM/DM [146].…”
Section: Serum Biomarkersmentioning
confidence: 78%
“…24 Bandoh et al found that the prognoses of six ILD-patients associated with PM/DM corresponded to the levels of KL-6. 25 In this study, KL-6 levels decreased in all of the patients who showed improved or unchanged CT fi ndings (Fig. 2).…”
Section: Discussionmentioning
confidence: 79%
“…56,57 Upon epithelial damage, KL-6 leaks into the circulation where it can be measured. It acts as a chemotactic factor, promoting the migration, proliferation and survival of lung fibroblasts.…”
Section: Krebs Von Den Lungen-6mentioning
confidence: 99%